2005
DOI: 10.1186/1475-925x-4-64
|View full text |Cite
|
Sign up to set email alerts
|

Fluid-structure interaction in abdominal aortic aneurysms: effects of asymmetry and wall thickness

Abstract: BackgroundAbdominal aortic aneurysm (AAA) is a prevalent disease which is of significant concern because of the morbidity associated with the continuing expansion of the abdominal aorta and its ultimate rupture. The transient interaction between blood flow and the wall contributes to wall stress which, if it exceeds the failure strength of the dilated arterial wall, will lead to aneurysm rupture. Utilizing a computational approach, the biomechanical environment of virtual AAAs can be evaluated to study the aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(112 citation statements)
references
References 28 publications
(28 reference statements)
6
100
1
5
Order By: Relevance
“…The results con¯rm that the healthy case reproduces a diameter change of about 2 mm in good agreement with clinical observations. 36 In the pathological scenarios, we recover radial displacements in agreement with the numerical results illustrated by Scotti et al 37 We carried out a model tuning also in terms of arterial wall stresses. Figure 5 shows the von Mises stress distributions for the di®erent models simulated.…”
Section: Model Tuningsupporting
confidence: 85%
“…The results con¯rm that the healthy case reproduces a diameter change of about 2 mm in good agreement with clinical observations. 36 In the pathological scenarios, we recover radial displacements in agreement with the numerical results illustrated by Scotti et al 37 We carried out a model tuning also in terms of arterial wall stresses. Figure 5 shows the von Mises stress distributions for the di®erent models simulated.…”
Section: Model Tuningsupporting
confidence: 85%
“…(2) and material formulations discussed above, were solved over a cardiac cycle using the commercial finite element code ADINA (ADINDA R&D, Watertown, MA). ADINA has been used extensively to model systems exhibiting material and geometric nonlinearity, and has been successfully employed to solve arterial FSI problems 20,39,46,50,51. We use ADINA to solve the strongly coupled nonlinear fluid and solid systems of equations in an iterative manner using in-core direct sparse solvers.…”
Section: Methodsmentioning
confidence: 99%
“…However, in their work, the wall and ILT were considered linearly elastic materials. The nonlinear behavior of the wall and ILT as well as more complex pulsatile flow conditions were modeled in a series of studies conducted by Scotti et al, 7476 which demonstrated the importance of considering the nonlinear elastic behavior of the structural domain. Moreover, the comparative study between FSI (coupled and decoupled) and structural analysis of patient-specific AAA performed by Scotti et al 75 show that the non-uniform pressure distribution on the inner AA surface due to the flow yielded a maximum peak wall stress up to 20% higher compared to that obtained with a static FEA when a uniform systolic pressure of 117 mmHg is applied.…”
Section: Biomechanical Factorsmentioning
confidence: 99%